Production of Alpha Amylase by Bacillus cereus in Submerged Fermentation - Helen H. Raplong; Peter O. Odeleye; Chrinius Hammuel; Matthew O. Idoko; Judy I. Asanato; Evelyn H. Odeke (Graduate Program of Syiah Kuala University, 2014)
Microorganisms have the ability to secrete enzymes when they are grown in the presence of certain substrates. Amylases are among the most important industrial enzymes and are of great significance in biotechnological studies. Bacteria belonging to the genus Bacillus were isolated using mannitol egg yolk polymyxin B (MYP) agar a highly selective media for Bacillus cereus isolation. The isolates were tested for α-amylase production on nutrient agar supplemented with starch and in submerged fermentation. The bacteria isolated and identified (using the Microgen Bacillus identification kit) were all Bacillus cereus and SB2 had the largest zone of hydrolysis of 12mm on nutrient agar supplemented with starch as well as the highest enzyme activity of 1.62U/ml. Amylase activity of 2.56U/ml was obtained after 24 hours incubation in submerged fermentation. When amylase enzyme production parameters where optimized, maximum amylase activity was obtained at a pH of 6.5, temperature of 350C, incubation time of 24 hours and 4% inoculums concentration. Bacillus cereus SB2 is a potential isolate for alpha-amylase production with soluble starch as the sole carbon source in submerged fermentation.